Clinical utility of cryptococcal antigen detection in transthoracic needle aspirate by lateral flow assay for diagnosing non-HIV pulmonary cryptococcosis: A multicenter retrospective study. Issue 37 (16th September 2022) - Hu, Qun; Li, Xiaohua; Zhou, Xiao; Zhao, Chunlei; Zheng, Caixia; Xu, Liyu; Zhou, Zizi
Abstract : Lateral flow immunoassay (LFA) detection of cryptococcal capsular polysaccharide antigen (CrAg) is reported to be the most rapid and convenient laboratory method for diagnosing cryptococcosis. Its clinical diagnostic use, however, is not well studied. We retrospectively analyzed the data from 97 patients with suspected pulmonary cryptococcosis (PC) at 2 tertiary care centers. CrAg in both serum and lung aspirate specimens were examined by LFA. We divided the patients who were diagnosed with PC into group I, patients positive for CrAg in both the serum and lung aspirate, and group II, patients positive for CrAg in the lung aspirate but not in the serum. We analyzed the differences in imaging distribution, morphological characteristics, and concomitant signs between the 2 groups. Of all 97 patients, 47 were diagnosed with PC. Lung aspirates were positive for CrAg in 46/47 patients with PC (sensitivity 97.9%, specificity 100%, positive predictive value = 100%, negative predictive value = 98%). There were no false positive results in the noncryptococcosis patients, revealing a diagnostic accuracy of 99%. Serum CrAg tests were positive in 36/47 patients with PC (sensitivity 76.6%, specificity 100%, accuracy 88.7%, positive predictive value = 100%, negative predictive value = 82%). Chest imaging data showed a statistically significant greater number of single lesions in group II than in group I ( P < .05). More lesions accompanied by halo signs were showed in group I ( P < .01), whereas more accompanied by pleural stretch signs were found in group II ( P < .01). The LFA-positive rate of CrAg in lung aspirate samples was higher than that of the serum samples, especially in patients with single pulmonary lesion or in those accompanied by pleural stretch. The direct measurement of CrAg in lung aspirate is a rapid, useful alternative diagnostic method for PC confirmation.